The darkdeep - Condie, Allyson Braithwaite (Bloomsbury Children's Books, 2018)
Middle-schoolers Nico, Tyler, Ella, and Opal discover a hidden island in a forbidden cove that appears uninhabited, but something ancient has awakened knowing their wishes, dreams, and darkest secrets.